2015
DOI: 10.1080/09540121.2015.1046416
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers to access to care reported by women living with HIV across 27 countries

Abstract: Increased access to successful antiretroviral therapy (ART) is necessary in order to achieve an AIDS-free generation. Importantly, slightly over half of the people living with HIV are women. Small studies have described many barriers to accessing treatment and care among women living with HIV. This cross-sectional, non-interventional, epidemiological study assessed the prevalence of barriers to accessing care for women living with HIV across 27 countries, divided into four global regions. HIV-positive women at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…As observed in other studies, the positive attitudes of HCWs have been correlated with high levels of HIV/AIDS and alcohol consumption knowledge [5,10,11,12,13,19], and also through on-going training [8]. …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As observed in other studies, the positive attitudes of HCWs have been correlated with high levels of HIV/AIDS and alcohol consumption knowledge [5,10,11,12,13,19], and also through on-going training [8]. …”
Section: Discussionmentioning
confidence: 53%
“…Those able to access medical care are living longer and have improved their health thanks to antiretroviral medications. These patients are experiencing acute HIV-related chronic episodes and other types of illness that can require hospitalization and/or supportive care arrangements [4,5]. Several studies have investigated the attitudes, knowledge and practices of health care workers (HCWs) towards patients with HIV/AIDS and underlined that HCWs still fear the disease and behave prejudicially toward HIV/AIDS patients [6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advances in prophylactic and therapeutic strategies, the transformation of HIV into a chronic medical condition where PLWH can be expected to have a normal life expectancy if receiving recommended treatment [3] has resulted in their health-related quality of life (HRQoL) emerging as a key focus for researchers and healthcare providers [4]. As with any other chronic illness, PLWH face numerous personal, social, mental, and physical comorbidities that can affect their HRQoL [5, 6]. The complex interplay between HIV and these comorbidities has generated an urgency to maximize the HRQoL experienced by PLWH [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that HIV/AIDS stigma is a barrier for PLWHA-seeking health care due to lack of community HIV/AIDS knowledge, lack of understanding supportive clinic environments, absence of personal financial resources,3 and lack of employment opportunities 4. Although attention to stigma has steadily increased, it is especially important to comprehensively understand HIV/AIDS stigma under a measurable conceptual framework from different individuals’ perspectives in order to improve access to HIV health care.…”
Section: Introductionmentioning
confidence: 99%